Nurses' experiences of participating in employee assistance program and factors influencing its effectiveness: a qualitative study - Fan, Xuanhao; Zhuang, Jiehao; Chen, Zhongqing; Xiong, Ziyi; Yang, Niu; Pu, Jiangfeng; Xu, Peng; Chen, Lifang; Huang, Huigen (Frontiers in Public Health, 2025)
IntroductionEmployee assistance program (EAP) as an effective modern method for improving the physical and mental health of nurses. To understand the experiences of clinical nurses participating in the EAP, to explore the relevant factors influencing its implementing effect, to provide reference for developing a more effective and reasonable EAP in healthcare organizations, to implement targeted assistance for nurses, and to promote the physical and mental health development of nurses.MethodsA descriptive research method was used to conduct semi-structured interviews with 14 clinical nurses. Interviews lasted between 25–40 min. The themes of the interview data were distilled through thematic analysis using NVivo 15 software. Sample size was subject to content saturation.ResultsThe mean age of the participants was 36.29 years, and the mean duration of clinical work was 14.07 years from different departments. Two themes and six sub-themes were identified for nurses' experience of participation in EAP. Seven themes and 15 sub-themes were identified as factors affecting the effectiveness of EAP implementation from the government, hospital, EAP, and nurse level.DiscussionThis study innovatively identified nurses' experience of participating in the EAP and the factors influencing its effectiveness obtained from a qualitative analysis perspective. Nurses could have a variety of positive experiences by participating in an EAP, with improved mental health status being the main focus. However, the long-term and professional nature of EAP was still deficient. This study found that there were a variety of factors affecting the effectiveness of EAP implementation, including the government's financial support, institutional safeguards, and the participation and support of hospital management, which were the prerequisites for the effectiveness of the program. The integration of multiculturalism and the enhancement of publicity could promote the two-way understanding between nurses and EAP, while ensuring that the EAP had long-term, flexible, targeted, and professional characteristics was key to its effective implementation. Therefore, in future studies, there remains a need for the government to establish universal team training and implementation programs, while hospitals must personalize applications and maintain sustained implementation to collect nurse feedback, thereby optimizing the EAP and safeguarding the occupational health of nurses.